Nananatiling Tahimik: Exploring the Lived Experience of Deaf Gay Workers in the Private Sector - Celebrado, Jan Erron R. (Review of Women's Studies, 2023)
This interpretative phenomenological study aims to document and examine the experience of discrimination against Deaf gay men workers at the intersection of their disability and gender, particularly in recruitment and selection, provisions of reasonable accommodation at work, and workplace participation. The results of the in-depth semi-structured interviews with seven Deaf gay men workers and key informant interviews with three experts reveal the role of patriarchy in the centrality of the able-bodied, heterosexual image in the workplace and these Deaf gay men's experience of distinct forms of discrimination on the basis of their disability and gender. Key themes that emerged include the convergence of gender and disability stereotypes, the ableist and heteronormative workplace practices, and the unequal power relations between Deaf gay men workers and their hearing heterosexual colleagues. The study recommends various workplace strategies such as (1) development and implementation of inclusive policies, (2) conduct of awareness-raising activities among employees and human resource professionals, and (3) adherence to the implementation of the law on reasonable accommodation. The study also seeks to advance the need to develop a feminist development approach that is markedly intersectional to capture the lived realities of marginalized people and communities holistically.